UPAYA MENINGKATKAN PENANAMAN PENDIDIKAN KARAKTER SISWA DENGAN MODEL PBL (PROBLEM BASED LEARNING) MELALUI MEDIA KARTUN ANIMASI NUSSA DAN RARA - SAFITRI, DEVI (JURNAL ILMU PENDIDIKAN, 2023)
The aim of this research is to improve the cultivation of student character education using the problem based learning (PBL) model through the animated cartoon media Nussa and Rara in class 1 of UPT SPF SDN 105359 Sumberjo. The method used in this research is the Classroom Action Research method using 2 cycles. The subjects of this research were 14 grade 1 students of UPT SPF SDN 105359 Sumberjo. The instruments used to obtain data were observation sheets, interview sheets, field notes and documentation during research. The data analysis technique used is the average number of students, the percentage of students who have completed and the percentage of students who have not completed. The results of the research showed that there was an increase from cycle I of 48% with an average value of 7.21, where in cycle I the results were obtained in the sufficient criteria, while in cycle II the results were obtained at 90% with an average value of 13.5 in the good criteria category.